Analysis of Volatile Compound at Different Age of Corn Crops Used as Bemisia tabaci Repellent - Retno Wikan Tyasningsiwi; Witjaksono Witjaksono; Siwi Indarti (Universitas Gadjah Mada, 2019)
Bemisia tabaci is one of the red chili pests that plays a role as a Begomovirus vector. This vector can be controlled through Integrated Pest Management (IPM) practices. One of the potential practices is by utilizing corn as a barrier crop to prevent the vector from attacking the main crop. The aim of this research was to examine the repellence activity of the volatile compound obtained from various ages of corn crop against B. tabaci. The volatile compound was collected from the corns at 4 week after planting (WAP), 6 WAP, 8 WAP, 10 WAP, and 12 WAP. Volatile compound capture device was designed with two solvents, i.e. hexane and ethanol, then the volatile compound analyzed by Gas Chromatography Mass Spectrometry (GC-MS). B. tabaci repellency against volatile compound was examined using Y-tube olfactometer. Each treatment was employed with 5 replications. Data were analyzed using ANOVA with 95% and further analyzed by Least Significant Different (LSD). The parameter observed was the total of B. tabaci avoided the volatile compound tested until half of the control olfactometer arm. The results showed that all ages of the corn produced repellent compound and the most optimal were corn aged 12 WAP with repellency rate of 83.72%. GC-MS analysis identified the volatile compound were citronella, limonene, β-phellandrene, β-caryophyllene, 1.8 cineole, farnesol, caryophyllene, and patchouli alcohol.